The Beneficience Of Religious Relaxation: Dzikir To Increase Phsycological Wellness Of Elder - Ah. Yusuf; Sriyono Sriyono; Iqlima Dwi Kurnia (Jurnal Ners, 2008)
Introduction: Psychological well-being is one of an important part on the positive aging process for elderly. Many older people face stressful situation such as death of family, deterioration of health, decrease of physical ability and psychological problem like loneliness, low self esteem, useless, isolation or difficulty in relationship. Religious relaxation: dzikir is one of the group therapy to fill up psychological necessary by filled up spiritual necessary so they could say thanks to God for everything what they have had now. The aimed of this study was to analyze the effect of religious relaxation: dzikir to increase the level of psychological well being of the elderly.Methods: This study was used a quasy experimental pre post test design. There were 20 respondents which taken by using purposive sampling. The independent variable was religious relaxation: dzikir and the dependent variable was elderly psychological well being. Data were analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U-Test with significance level a≤0.05.Results: The result showed that religious relaxation: dzikir has an effect on increasing the level of psychological well being of the elderly with Wilcoxon Signed Rank Test p=0.004 in treatment group, p=1.000 in control group and the result of Mann Whitney U-Test revealed p=0.000.Conclusion: It can be concluded that religious relaxation: dzikir can increase psychological well-being. Religious relaxation: dzikir help the elderly to develop self acceptance, autonomy, positive relation with others, environmental mastery, purposive in life and personal growth. Researcher suggests the institutional to practice relaxation religious: dzikir to help elderly people to raise psychological well-being.